The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00192-016-2958-z
|View full text |Cite
|
Sign up to set email alerts
|

Endopelvic free anchor minisling technique for stress urinary incontinence treatment: 10 years of experience

Abstract: EFA is a viable, safe, and effective technique for treating UI due to urethral hypermobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although SIS procedure could be performed with concomitant pelvic reconstructive surgery, data is scarce. Most of the studies that reported SIS results in patients with SUI, excluded the patients with genital prolapse (13,15,29). Fernandez-Gonzalez et al included patients with genital prolapse to their study which compared SIS (Contasure needless®) with TOT (Monarch®) in treatment of SUI and found Contasure needless® was not inferior to Monarch® (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SIS procedure could be performed with concomitant pelvic reconstructive surgery, data is scarce. Most of the studies that reported SIS results in patients with SUI, excluded the patients with genital prolapse (13,15,29). Fernandez-Gonzalez et al included patients with genital prolapse to their study which compared SIS (Contasure needless®) with TOT (Monarch®) in treatment of SUI and found Contasure needless® was not inferior to Monarch® (12).…”
Section: Resultsmentioning
confidence: 99%
“…To minimize these risks, single incision slings (SIS) that avoids retropubic or obturator space entry, have developed in 2006 (9). Despite potential advantages of SIS, reported cure rate ranges from 48-88% in 2-5 years follow-up (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Although SIS procedure could be performed with concomitant pelvic reconstructive surgery, data is scarce. Most of the studies that reported results of SIS procedure in patients with SUI excluded the patients with pelvic prolapse (16,18,32). Fernandez-Gonzalez et al included patients with pelvic prolapse in their study, which compared SIS (Contasure needless®) with TOT (Monarch®) in the treatment of SUI.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the objective cure and failure rates were 83% and 9.8%, respectively (32). Moreover, Gambini-Ricapa et al published high urodynamically proven cure rate after endopelvic free anchor mini-sling procedures at long follow-up and suggested that the success of the mini-sling technique was due to retropubic insertion route of sling to endopelvic fascia and pelvic diaphragm (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation